Constructive Termination of Employment by Indonesia Companies: A Comparative Study - Kasih, Desak Putu Dewi; Satyayuda Dananjaya, Nyoman; Sudiarawan, Kadek Agus; Raksita, I Putu Bimbisara Wimuna (Susbtantive Justice International Journal of Law, 2021)
This research aims to identify the regulation and dispute resolution regarding constructive termination of employment by a company in the perspective of Indonesian Labor Law. This research also compares the constructive termination of employment by companies based on International Law and Japan Labor Law. This is normative legal research with a statutory approach, conceptual approach, and also comparative law approach. The result shows that the constructive termination of employment has not been specifically regulated in the Indonesian Labor Law system, hence it becomes an exploitation gap that is used by companies to be able to terminate employment relations without protecting the worker’s right. The dispute resolution mechanism in terms of constructive termination of employments still refers to the provisions of the Industrial Relations Dispute Settlement Law, namely through bipartite negotiations, tripartite, and industrial relations courts. The constructive termination of employment has been substantively regulated in the ILO Convention C-158 concerning the Termination of Employment, which regulated in Article 4 to Article 6. Further in Japan, the constructive termination of employment is regulated in the Japan Labor Union Act, Act Number 174 of 1949 in Article 7 paragraph (i), (iii), and (iv) with its national enforcement.